2023
DOI: 10.1155/2023/5823207
|View full text |Cite
|
Sign up to set email alerts
|

Application of Nanocellulose Biofilter from Pineapple Peel Waste for Water Microbes Removal

Abstract: This research aimed to assess the effectiveness of nanocellulose biofilter (NCB) made from pineapple peel waste to reduce the number of microbes in water. Further processing of cellulose from nata de pina into nano size was proposed, then transformed into a filter membrane. Three types of NCB were developed: bacterial cellulose acetate membrane, bacterial cellulose acetate membrane with TiO2 treatment, and bacterial cellulose acetate membrane with TiO2 and graphite nanoplatelet treatment. These NCBs were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The result of untreated water was (120MPN/100ml) for the both samples. Filtration and addition of Acacia ( Acacia Nilotica) reduce the microbial load for the surface sample to (4MPN/100ml) compared to a reduction of (7 MPN/100ml ), for ground sample when treated by ltration, the water sample collected from surface source followed the same trend for that of water collected from ground source when treated with Acacia, were high reduction of microbial load was noted (4 MPN/100ml) for surface sample compared to (11MPN/100ml ) for ground sample (Rini et al, 2023).…”
Section: Discussionmentioning
confidence: 80%
“…The result of untreated water was (120MPN/100ml) for the both samples. Filtration and addition of Acacia ( Acacia Nilotica) reduce the microbial load for the surface sample to (4MPN/100ml) compared to a reduction of (7 MPN/100ml ), for ground sample when treated by ltration, the water sample collected from surface source followed the same trend for that of water collected from ground source when treated with Acacia, were high reduction of microbial load was noted (4 MPN/100ml) for surface sample compared to (11MPN/100ml ) for ground sample (Rini et al, 2023).…”
Section: Discussionmentioning
confidence: 80%
“…Nanocellulose was obtained from pineapple peel waste. In the investigation, the amount of microbes was measured in the water before and after filtration, and it was found that the amount of microbes decreased by about 50% [90].…”
Section: Various Applications Of Nanocellulosementioning
confidence: 99%
“…Investing in cleaner technologies, such as ultrasound and microwaves, could help [100]; (4) Develop economic industrial processes to market nanocelluloses for various applications. In this sense, the companies Diacel FineChem Ltd. (Japan) and Celluforce (Canada) are producing nanocelluloses on a large scale [100]; (5) Using, from a bioeconomy and circular economy perspective, agricultural and forestry residues for the production of nanocelluloses [100], such as pineapple peel [90], banana stems [86], or corn straw [91].…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%